IDENTIFIKASI NILAI-NILAI KARAKTER DALAM BUKU TEKS KURIKULUM 2013 TEMA 5 PENGALAMANKU PADA KELAS I SEKOLAH DASAR - Irawati, Irawati; Makmun, Makmun; Warsinah, Warsinah (Tunas: Jurnal Penelitian Pendidikan Dasar, 2021)
This research is motivated by the books being recalled and disturbing the world of education, not just general textbooks. However, there are also religious books that were withdrawn from circulation because they contained deviant teachings. The aim is to describe the character values in the 2013 curriculum theme 5 My Experience and the benefits of this research can be used as a reference for improving character through an integration model in elementary school subject matter and also as a reference in the improvement of subsequent books and used as a guide for book users. 2013 curriculum text. This research is a Content Analysis research with the sub-theme subject in the 2013 Curriculum Textbook, My Experience theme. As the object of research is the character values contained in the textbook. This research technique was carried out by analyzing and recording carefully the 2013 Curriculum Theme 5 My Experience textbook in the first semester of the second semester of Elementary School. The content analysis technique used in this study uses a content analysis technique consisting of six steps. The six steps are, "Unitizing, sampling, recording, reducing, inferring, narrating".